2020
DOI: 10.1158/0008-5472.can-19-1145
|View full text |Cite
|
Sign up to set email alerts
|

Integrin β4–Targeted Cancer Immunotherapies Inhibit Tumor Growth and Decrease Metastasis

Abstract: Integrin b4 (ITGB4) has been shown to play an important role in the regulation of cancer stem cells (CSC). Immune targeting of ITGB4 represents a novel approach to target this cell population, with potential clinical benefit. We developed two immunologic strategies to target ITGB4: ITGB4 protein-pulsed dendritic cells (ITGB4-DC) for vaccination and adoptive transfer of anti-CD3/ anti-ITGB4 bispecific antibody (ITGB4 BiAb)-armed tumordraining lymph node T cells. Two immunocompetent mouse models were utilized to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 43 publications
2
55
0
Order By: Relevance
“…Furthermore, the prophylactic use of granulocyte-colony stimulating factor in Japanese patients was approved in 2014; therefore, the higher incidence of febrile neutropenia in this study is not thought to be a significant concern in practice. In support of this, in the phase III randomized PEONY trial of Asian patients with early/locally advanced HER2 breast cancer treated with pertuzumab plus trastuzumab and docetaxel, concomitant use of prophylactic granulocyte-colony stimulating factor was permitted, with only four patients (1.8%) reported to develop febrile neutropenia [ 19 ]. Similar to the results observed in our study, a subgroup analysis of Asian patients in CLEOPATRA demonstrated a higher incidence of febrile neutropenia in Asian patients than in patients from other regions [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the prophylactic use of granulocyte-colony stimulating factor in Japanese patients was approved in 2014; therefore, the higher incidence of febrile neutropenia in this study is not thought to be a significant concern in practice. In support of this, in the phase III randomized PEONY trial of Asian patients with early/locally advanced HER2 breast cancer treated with pertuzumab plus trastuzumab and docetaxel, concomitant use of prophylactic granulocyte-colony stimulating factor was permitted, with only four patients (1.8%) reported to develop febrile neutropenia [ 19 ]. Similar to the results observed in our study, a subgroup analysis of Asian patients in CLEOPATRA demonstrated a higher incidence of febrile neutropenia in Asian patients than in patients from other regions [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, one DC-based vaccine targets integrin β4, which is overexpressed in breast and colon cancers and plays a role in CSC self-renewal. The humoral and cellular immune responses elicited by this vaccine are effective in inhibiting tumor growth and spontaneous pulmonary metastases as they kill both CSCs and differentiated cancer cells (52).…”
Section: Cancer Stem Cell Oncoantigens As Targets For Vaccinationmentioning
confidence: 99%
“…The results obtained from the MUC1-vaccine trials suggest that, like all monotherapies, single immunotherapy is insufficient for cancer treatment, and that combinatorial approaches are needed (Figure 1). Several studies on preclinical models of melanoma, breast, colon and head and neck squamous cell carcinomas (HNSCC) have shown that combining CSC-targeting vaccines with ICIs induces increased activation of tumor-specific CD8 + T cells, decreased CSC frequency and better tumor-progression control than single treatments, paving the way for clinical experimentation (33,52,63,64).…”
Section: Combination Therapiesmentioning
confidence: 99%
“…It has been reported that ITGB3dependent uptake of extracellular vesicles, for which focal adhesion kinase is required as a key role, could promote the metastasis of breast cancer cells [34]. ITGB4 and ITGB6 targeted immunotherapy is a promising strategy, showing a great effect on the inhibition of the progression and metastasis of tumors [35,36]. Studies have also suggested that ITGB7 and ITGB8 have the potential to mediate the progression of tumors, paving the way for a novel therapeutic approach for the treatment for cancers [37][38][39].…”
Section: Discussionmentioning
confidence: 99%